Progress of potential drugs targeted in lipid metabolism research - Liang, Kai; Dai, Jian-Ye (Frontiers in Pharmacology, 2022)
Lipids are a class of complex hydrophobic molecules derived from fatty acids that not only form the structural basis of biological membranes but also regulate metabolism and maintain energy balance. The role of lipids in obesity and other metabolic diseases has recently received much attention, making lipid metabolism one of the attractive research areas. Several metabolic diseases are linked to lipid metabolism, including diabetes, obesity, and atherosclerosis. Additionally, lipid metabolism contributes to the rapid growth of cancer cells as abnormal lipid synthesis or uptake enhances the growth of cancer cells. This review introduces the potential drug targets in lipid metabolism and summarizes the important potential drug targets with recent research progress on the corresponding small molecule inhibitor drugs. The significance of this review is to provide a reference for the clinical treatment of metabolic diseases related to lipid metabolism and the treatment of tumors, hoping to deepen the understanding of lipid metabolism and health.